Integral Formulae of Bernoulli Polynomials - Dae San Kim; Dmitry V. Dolgy; Hyun-Mee Kim; Sang-Hun Lee; Taekyun Kim (Discrete Dynamics in Nature and Society)
Recently, some interesting and new identities are introduced in (Hwang et al., Communicated). From these identities, we derive some new and interesting integral formulae for the Bernoulli polynomials.